Multiplicity dependence of ϒ production at forward rapidity in pp collisions at √𝑠 = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Nuclear physics. B, Particle physics, 2025)
The measurement of ϒ(1S), ϒ(2S), and ϒ(3S) yields as a function of the charged-particle multiplicity density, dNch/dη, using the ALICE experiment at the LHC, is reported in pp collisions at s= 13 TeV. The ϒ meson yields are measured at forward rapidity (2.5<y<4) in the dimuon decay channel, whereas the charged-particle multiplicity is defined at central rapidity (|η|<1). Both quantities are divided by their average value in minimum bias events to compute the self-normalized quantities. The increase of the self-normalized ϒ(1S), ϒ(2S), and ϒ(3S) yields is found to be compatible with a linear scaling with the self-normalized dNch/dη, within the uncertainties. The self-normalized yield ratios of excited-to-ground ϒ states are compatible with unity within uncertainties. Similarly, the measured double ratio of the self-normalized ϒ(1S) to the self-normalized J/ψ yields, both measured at forward rapidity, is compatible with unity for self-normalized charged-particle multiplicities beyond one. The measurements are compared with theoretical predictions incorporating initial or final state effects.
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Bórquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yüncü, F. Zanone, [und 1026 weitere]
Online verfügbar: 20. Dezember 2024, Artikelversion: 13. Januar 2025
Gesehen am 18.09.2025